Non-linear viscoelastic modelling of earthquake-induced strcutural pounding. - Jankowski, Robert (Earthquake engineering & structural dynamics.)
Past severe earthquakes indicate that structural pounding may cause considerable damage or even lead to collapse of colliding structures if the separation distance between them is not sufficient. Because of its complexity, modelling of impact is an extremely difficult task, however, the precise numerical model of pounding is essential if an accurate structural response is to be simulated. The aim of this paper is to analyse a non-linear viscoelastic model of collisions which allows more precise simulation of the structural pounding during earthquakes. The effectiveness of the model is verified by comparing the results of numerical analyses with the results of experiments conducted on pounding between different types of structures. The results of the study indicate that, compared to other models, the proposed non-linear viscoelastic model is the most precise one in simulating the pounding involved structural response.